ATPase Activity of the Subcellular Fractions of Colorectal Cancer Samples under the Action of Nicotinic Acid Adenine Dinucleotide Phosphate - Kushkevych, Ivan; Bychkov, Mykola; Bychkova, Solomiia; Gajdács, Márió; Merza, Romana; Vítězová, Monika (Biomedicines, 2021)
In tumor cells with defects in apoptosis, autophagy allows prolonged survival. Autophagy leads to an accumulation of damaged mitochondria by autophagosomes. An acidic environment is maintained in compartments of cells, such as autophagosomes, late endosomes, and lysosomes; these organelles belong to the "acid store" of the cells. Nicotinic acid adenine dinucleotide phosphate (NAADP) may affect the release of Ca2+ from these organelles and affect the activity of Ca2+ ATPases and other ion transport proteins. Recently, a growing amount of evidence has shown that the variations in the expression of calcium channels or pumps are associated with the occurrence, disease-presentation, and the prognosis of colorectal cancer. We hypothesized that activity of ATPases in cancer tissue is higher because of intensive energy metabolism of tumor cells. The aim of our study was to ascertain the effect of NAADP on ATPase activity on tissue samples of colorectal cancer patients' and healthy individuals. We tested the effect of NAADP on the activity of Na+/K+ ATPase; Ca2+ ATPase of endoplasmic reticulum (EPR) and plasma membrane (PM) and basal ATPase activity. Patients' colon mucus cancer samples were obtained during endoscopy from cancer and healthy areas (control) of colorectal mucosa of the same patients. Results. The mean activity of Na+/K+ pump in samples of colorectal cancer patients (n = 5) was 4.66 ± 1.20 μmol Pi/mg of protein per hour, while in control samples from healthy tissues of the same patient (n = 5) this value was 3.88 ± 2.03 μmol Pi/mg of protein per hour. The activity of Ca2+ ATPase PM in control samples was 6.42 ± 0.63 μmol Pi/mg of protein per hour and in cancer -8.50 ± 1.40 μmol Pi/mg of protein per hour (n = 5 pts). The mean activity of Ca2+ ATPase of EPR in control samples was 7.59 ± 1.21 μmol Pi/mg versus 7.76 ± 0.24 μmol Pi/mg in cancer (n = 5 pts). Basal ATPase activity was 3.19 ± 0.87 in control samples versus 4.79 ± 1.86 μmol Pi/mg in cancer (n = 5 pts). In cancer samples, NAADP reduced the activity of Na+/K+ ATPase by 9-times (p < 0.01) and the activity of Ca2+ ATPase EPR about 2-times (p < 0.05). NAADP caused a tendency to decrease the activity of Ca2+ ATPase of PM, but increased basal ATPase activity by 2-fold vs. the mean of this index in cancer samples without the addition of NAADP. In control samples NAADP caused only a tendency to decrease the activities of Na+/K+ ATPase and Ca2+ ATPase EPR, but statistically decreased the activity of Ca2+ ATPase of PM (p < 0.05). In addition, NAADP caused a strong increase in basal ATPase activity in control samples (p < 0.01). Conclusions: We found that the activity of Na+/K+ pump, Ca2+ ATPase of PM and basal ATPase activity in cancer tissues had a strong tendency to be higher than in the controls. NAADP caused a decrease in the activities of Na+/K+ ATPase and Ca2+ ATPase EPR in cancer samples and increased basal ATPase activity. In control samples, NAADP decreased Ca2+ ATPase of PM and increased basal ATPase activity. These data confirmed different roles of NAADP-sensitive "acidic store" (autophagosomes, late endosomes, and lysosomes) in control and cancer tissue, which hypothetically may be connected with autophagy role in cancer development. The effect of NAADP on decreasing the activity of Na+/K+ pump in cancer samples was the most pronounced, both numerically and statistically. Our data shows promising possibilities for the modulation of ion-transport through the membrane of cancer cells by influence on the "acidic store" (autophagosomes, late endosomes and lysosomes) as a new approach to the treatment of colorectal cancer.